EFEKTIVITAS PEMBELAJARAN ROBOTIKA TERSTRUKTUR BERBASIS ELEKTRONIKA PRAKTIS UNTUK SISWA SEKOLAH DASAR - yon, agung; Sidqon, Mochamad; Breva Yunanda, Anton; kusnanto, Geri; Yuwono, Istantyo (Journal of Science and Social Development, 2024)
Abstract. This study evaluates the effectiveness of a robotics learning approach starting with practical electronics, analog robot design, and basic mechanics in enhancing elementary school students' interest in learning. The research also explores how students’ economic backgrounds influence their enthusiasm for robotics education. The subjects were 25 fifth-grade students from SDN Margorejo 1 Surabaya, selected based on specific criteria, including middle-income family backgrounds. The quasi-experimental research design included pre-test and post-test stages. Activities comprised four phases: introduction to practical electronics, simple analog robot design, basic robotics mechanics training, and robot integration and testing. Data were collected through questionnaires, observations, interviews, and project assessments. Descriptive analysis and non-parametric statistical tests measured changes in students’ interest, while qualitative methods examined economic factors affecting enthusiasm. Results revealed a 23% average increase in students’ interest in robotics. Additionally, 88% of students successfully built simple robots demonstrating creativity and functionality. Students from middle-income families maintained high enthusiasm, showing that economic constraints did not significantly hinder participation. This integrated approach effectively fosters technological interest, aligns with STEM concepts, and prepares students for technology-driven challenges. The study contributes practically and theoretically to robotics learning models for elementary education. Keywords: Robotics, Practical Electronics, Learning Interest, Elementary School, Middle-Income Economy, STEM